The non-proportionality of local stress paths in engineering applications - C. Riess; M. Obermayr; M. Vormwald (Fracture and Structural Integrity)
A scalar measure, which describes the non-proportionality of local stress paths in engineering applications, is introduced. For this purpose the moment of inertia approach by Meggiolaro is modified in a way that the stress time history is evaluated in a tresca-stress-space. This modification makes the non-proportionality factor invariant with respect to the coordinate system. An optimization procedure is implemented to derive a test set-up for new component tests with 2 load channels. The aim of the planned tests is to get a high non-proportionality at the potential crack initiation site. It is not possible to obtain a high non-proportionality factor at the failure location without selective weakening of the component (housing of a rear axle steering). Therefore specific areas of the structure are cut out and the optimization procedure is repeated. As a result of the optimization a test set-up with high local non-proportionality at the potential crack initiation site is achieved for the weakened structure. Another set-up with slightly less non-proportionality but with a very localized damage is derived. This set-up is preferred, because of the robustness in the physical test.